Biogenic calcite particles from microalgae—Coccoliths as a potential raw material. Issue 6 (10th February 2017) - Jakob, Ioanna; Chairopoulou, Makrina Artemis; Vučak, Marijan; Posten, Clemens; Teipel, Ulrich
Abstract : Synthetic calcite (CaCO3 ) particles are found in a broad range of applications. The geometry of particles produced from limestone or precipitation are versatile but limited to basic shapes. The microalga Emiliania huxleyi produces micro‐structured calcite platelets, called coccoliths. This article presents the results of an application‐orientated study, which includes characteristic values also used in the calcite industry for particle evaluation. It is demonstrated that coccoliths are significantly different from all industrial particles produced so far. Coccoliths are porous particles, mainly consisted of calcium carbonate, with further elements such as Mg, Si, Sr, and Fe often embedded in their structure. Their structure is extremely sophisticated, while the overall particle morphology and particle size distribution are homogeneous. This study gives a first inside into the potential of these exceptional objects and may set further impulses for their utilization in specific calcite particle applications.